Immobilization of microalgae Chlorella vulgaris for biomass recovery and fatty acid methyl ester production - Noor Raihana, Abu Sepian (2021)
Microalgae had known to be a promising source for biofuel production as it can produce oil and grown faster than conventional crops. However, the small size of microalgae brings difficulties in the separation process. Thus, the immobilization method was introduced since it does not require energy and a comparison of this method with free cells culture was made initially. Alginate is the most widely used matrix but using alginate alone can cause bead rupture. Thus, a new combination of a matrix was implemented to improve the stability and cell growth. The screening and optimization of the factors affecting the immobilized microalgae cell growth were performed to obtain the maximum number of cell growth. The expensive Bold Basal Medium (BBM) had urged the usage of palm oil mill effluent (POME) as a cultivation medium since it is abundant in Malaysia. The microalgae Chlorella vulgaris 211/11B cells were immobilized within three novel combinations of matrices namely (1) mixed matrices, SACMCCA (SA: sodium alginate, CMC: sodium carboxymethyl cellulose, CA: calcium alginate) (2) SACA and (3) SACMC. The suitable matrix-to-microalgae volume ratios (0.2:1 – 1:1) were determined by evaluating the number of cell growth. Subsequently, the immobilized microalgae were screened and optimized using fractional factorial design (FFD) and central composite design (CCD). Five factors inducing the number of cell growth and cell loss of immobilized C. vulgaris including photoperiod, cultivation period, the concentration of glucose, sodium nitrate (NaNO3) and calcium chloride (CaCl2) were screened through 16 experiments generated from the system. The potential of palm oil mill effluent (POME) as a cultivation medium was investigated through different concentrations of POME (20 % - 100 %) mixed with distilled water (DW) and Bold Basal Medium (BBM). Meanwhile, studies on the kinetic and thermodynamic parameters were exhibited to understand the nature of extraction of immobilized microalgae using the reaction rate equation and Gibb’s free energy equation. The immobilized microalgae of mixed matrices with a ratio of 0.3:1 exhibited the highest number of cells with 1.72 × 109 cells/mL at day 10 and 30.43 % of oil extraction yield followed by SACA (0.3:1) (24.29 %), SACMC (1:1) (13.00 %), and SA (1:1) (6.71 %). Through the screening process using FFD, photoperiod and cultivation days were identified as the significant factors for both responses. The outcomes indicated that FFD is a convenient tool to determine the important factors for immobilized cell growth and increased lipid production by 17.27 %. Then, the two significant factors were optimized by central composite design (CCD). The suggested conditions obtained from FFD and CCD were 5.03 g/L of NaNO3, 1 w/v % of CaCl2, 24 h of photoperiod, 23.99 g/L of glucose and 7.96 cultivation days. The optimization using CCD had increased the lipid yield to 51.6 %. Meanwhile, 20 % POME mixed with 80 % DW showed a quite comparable lipid yield (38.14 ± 2.2 %) with the lipid obtained from BBM (48.03 ± 3.7 %). The kinetic studies showed that the values of the rate constants relied strongly on temperature. The thermodynamic studies revealed that the lipid extraction of immobilized microalgae biomass is an endothermic, irreversible and spontaneous reaction. The combination of SA, CA, and CMC made a new structure that enhanced the growth of C. vulgaris cells and increased the lipid production than the immobilization using a single matrix. Moreover, the FAME profile obtained from all the experimental works shows a high prospective for biodiesel production.